Visual C# 2010 Recipes A Problem-Solution Approach - Jones, Allen; MacDonald, Matthew; Rajan, Rakesh; Freeman, Adam (Apress : Imprint: Apress, 2010)
Mastering the development of .NET 4.0 applications in C# is less about knowing the Visual C# 2010 language and more about knowing how to use the functionality of the .NET framework class library most effectively. Visual C# 2010 Recipes explores the breadth of the .NET Framework class library and provides specific solutions to common and interesting programming problems. Each recipe is presented in a succinct problem/solution format and is accompanied by a working code sample to help you understand the concept and quickly apply it. When you are facing a Visual C# 2010 problem, this book likely contains a recipe providing the solution-or at least points you in the right direction. Even if you are simply looking to broaden your knowledge of the .NET framework class library, Visual C# 2010 Recipes is the perfect resource to assist you. This is an updated reference for .NET 4.0 programmers. All code samples come as stand-alone Visual Studio 2010 solutions for your convenience.